2019
DOI: 10.1002/bit.26906
|View full text |Cite
|
Sign up to set email alerts
|

Spatial modulation and cofactor engineering of key pathway enzymes for fumarate production in Candida glabrata

Abstract: Fumarate is a naturally occurring organic acid that is an intermediate of the tricarboxylic acid (TCA) cycle and has numerous applications in food, pharmaceutical, and chemical industries. However, microbial fumarate production from renewable feedstock is limited by the intrinsic inefficiency of its synthetic pathway caused by week metabolites transportation and cofactor imbalance. In this study, spatial modulation and cofactor engineering of key pathway enzymes in the reductive TCA pathway were performed for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(7 citation statements)
references
References 40 publications
0
7
0
Order By: Relevance
“…Regulation of PEP synthetase A and glyceraldehyde‐3‐phosphate dehydrogenase via promoter engineering has balanced the level of precursors required in isoprenoid biosynthesis in E. coli (Juyoung Jung et al, 2016). Similarly, promoter engineering of ADP‐dependent PEP carboxykinase and NAD + ‐dependent formate dehydrogenase fine‐tuned the cofactor balance for fumarate production in Candida glabrata (X. L. Chen et al, 2019). Hence, promoter engineering could effectively balance the supply of PEP and E4P.…”
Section: Introductionmentioning
confidence: 99%
“…Regulation of PEP synthetase A and glyceraldehyde‐3‐phosphate dehydrogenase via promoter engineering has balanced the level of precursors required in isoprenoid biosynthesis in E. coli (Juyoung Jung et al, 2016). Similarly, promoter engineering of ADP‐dependent PEP carboxykinase and NAD + ‐dependent formate dehydrogenase fine‐tuned the cofactor balance for fumarate production in Candida glabrata (X. L. Chen et al, 2019). Hence, promoter engineering could effectively balance the supply of PEP and E4P.…”
Section: Introductionmentioning
confidence: 99%
“…The reductive TCA pathway has been successfully applied to the biosynthesis of various organic acids by virtue of its high theoretical yield advantages. For example, even if there was no decarboxylation step in the glyoxylic acid pathway, the theoretical yield would be only 1 mol of succinic acid per mol of glucose, but the theoretical yield using the reductive TCA pathway would be 2 mol of succinic acid per mol of glucose . The reason for this is that there is a carbon fixation reaction in the reductive TCA pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Metabolic engineering is conducted to rewire the complete noncyclic glyoxylate pathway for fumarate production. Recently, five metabolic engineering strategies have been developed to enhance production of fumarate: reconstructing synthetic pathway, such as the reductive TCA cycle [ 2 ], the oxidative TCA cycle [ 3 ], the noncyclic glyoxylate cycle [ 4 ], the urea cycle and the purine nucleotide cycle [ 27 , 28 ]; eliminating byproducts formation [ 27 ], such as lactate, acetate, formate, malate, and succinate; optimizing oxidation and reduction levels [ 5 ]; modifying glucose transport system [ 8 ]; regulating C 4 -dicarboxylate transporter [ 26 ]. These results indicated that fumarate production has been improved by metabolic engineering strategies.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, fumarate is mainly produced through three major metabolic pathways, including the reductive TCA cycle [ 2 ], the oxidative TCA cycle [ 3 ], and the noncyclic glyoxylate cycle [ 4 ]. The maximum theoretical yield of fumarate is 2 mol/mol glucose in reductive TCA cycle, but its fumarate productivity is limited due to two reversible reactions catalyzed by malate dehydrogenase and fumarase [ 5 ]. Based on this reductive TCA cycle, fumarate productivity was increased to 0.30 g/L/h by combinatorially regulating the expression of phosphoenolpyruvate carboxykinase and formate dehydrogenase [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation